Physiological and anatomical consequences of infraorbital nerve transection in the trigeminal ganglion and trigeminal spinal tract of the adult rat - Renehan, WE (J Neurosci, 1989)
Single-unit recording and retrograde tracing techniques were used to assess the receptive field properties, topography, and projections of rat trigeminal primary afferent neurons subsequent to transection of the infraorbital (IO) nerve in adulthood. Four hundred and fifty-eight units were recorded in the trigeminal ganglion ipsilateral to nerve section. Of these, 66.6% had IO receptive fields. Thirty percent responded to innocuous stimulation of vibrissae, 39.1% to guard hair deflection, 8.2% to gentle indentation or stretch of the skin, and 22.3% to noxious stimuli (compared to 77.2% vibrissa, 12.0% guard hair, 4.5% skin, and 6.3% noxious in normal animals). An additional 15 units were driven by a stimulating electrode placed on the IO nerve proximal to the site of the lesion but had no receptive field. Of the cells with vibrissa receptive fields, 33.3% were slowly adapting type I (SAI), 6.6% were slowly adapting type II (SAII), 32.2% were low velocity rapidly adapting (RA-LV), 20.0% were high velocity rapidly adapting (RA- HV), and 7.7% were nociceptive (NX, in normal animals 43.8% were SAI, 10.3% SAII, 27.6% RA-LV, 16.8% RA-HV, and 1.5% NX). A number of cells had receptive field properties not seen in normal animals. The single- unit recordings indicated that the topography of mandibular and ophthalmic representations in the ganglion were essentially normal, while the organization of the maxillary region of the ganglion was slightly abnormal. The ganglion physiology experiments were augmented by records from primary afferents in the trigeminal spinal tract (TrV). Eighty-one (72.2%) of the 112 fibers recorded in the TrV of normal rats had IO receptive fields. Of these, 73.2% responded to innocuous vibrissal stimulation, 14.6% to guard hair deflection, 8.5% to gentle indentation of the skin, and 2.5% to noxious stimuli. Of the 61 vibrissa units, 37.8% were SAI, 19.7% SAII, 37.8% RA-LV, 3.3% RA-HV, and 1.6% NX. In adult-lesioned animals, 81 (61.3%) of the recorded fibers had IO receptive fields. Of this number, 38.2% responded to vibrissae, 29.6% to guard hairs, 16.0% to skin, and 19.7% to noxious simuli. Of the vibrissa-sensitive units, 16.1% were SAI, 3.2% were SAII, 45.2% were RA-LV, 35.5% were RA-HV, and 3.2% NX. As in the ganglion recording studies, a number of abnormal receptive fields were documented.(ABSTRACT TRUNCATED AT 400 WORDS)